2020
DOI: 10.1136/jmedgenet-2019-106657
|View full text |Cite
|
Sign up to set email alerts
|

POT1 mutation spectrum in tumour types commonly diagnosed among POT1-associated hereditary cancer syndrome families

Abstract: BackgroundThe shelterin complex is composed of six proteins that protect and regulate telomere length, including protection of telomeres 1 (POT1). Germline POT1 mutations are associated with an autosomal dominant familial cancer syndrome presenting with diverse malignancies, including glioma, angiosarcoma, colorectal cancer and melanoma. Although somatic POT1 mutations promote telomere elongation and genome instability in chronic lymphocytic leukaemia, the contribution of POT1 mutations to development of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…This figure comprises both missense and truncating mutations (2.3%, n = 10/444), as well as gene copy number amplifications (1.8%, n = 8/444). Similarly, Shen et al found that non-benign POT1 variants were observed in 3.7% of melanoma cases examined ( n = 64/1735) [ 65 ] ( Figure 2 ).…”
Section: Germline and Somatic Pot1 Mutations Inmentioning
confidence: 69%
See 4 more Smart Citations
“…This figure comprises both missense and truncating mutations (2.3%, n = 10/444), as well as gene copy number amplifications (1.8%, n = 8/444). Similarly, Shen et al found that non-benign POT1 variants were observed in 3.7% of melanoma cases examined ( n = 64/1735) [ 65 ] ( Figure 2 ).…”
Section: Germline and Somatic Pot1 Mutations Inmentioning
confidence: 69%
“…A recent pan-cancer study of POT1 mutations categorized genetic variants according to the standards of the American College of Medical Genetics and Genomics, and referred collectively to all POT1 variants that are neither “presumed benign” nor “benign” as “non-benign”. By this classification, 2.9% of tumors ( n = 1834/62,368) were found to have non-benign POT1 mutations [ 65 ]. Among the tumor categories with more than 50 cases, angiosarcoma (23.3%, n = 20/86) and cutaneous squamous cell carcinoma (9.1%, n = 20/220) had the highest prevalence of POT1 mutations [ 65 ] ( Figure 2 ).…”
Section: Germline and Somatic Pot1 Mutations Inmentioning
confidence: 99%
See 3 more Smart Citations